Levels of physical activity, physical and psychological well-being of university students, during the COVID-19 pandemic - Gibelli, Giovana [UNESP]; Moraes, Mayra Grava de [UNESP]; Teodoro, Marina Alves [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP] (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2024)
The objective of the study was to evaluate the levels of physical activity practice and psychological well-being of university students, of both sexes, during the COVID-19 pandemic. We opted for the cross-sectional experimental design method, when addressing the variables of physical exercise, stress, depression and anxiety that were manipulated and combined to verify a greater change in the responses to be analyzed in the research proposal, that is, that greater levels of physical exercises would be related to minor negative symptoms in the sphere of mental health. The results showed that, according to the sample collected, the proposed relationship was not verified, since the prevalence rates of symptoms of anxiety, depression and stress showed normal rates, without scores that indicate significant severity in the health condition mental health, and thus not proving, in this study, that the time of weekly physical activity had a direct influence on the mental health of the evaluated individuals, either in the improvement or reduction of the negative symptoms. Thus, it was verified that the Brazilian university students of the respective sample, despite not having adequate levels of physical activity practice, presented mental health conditions with a low prevalence of negative symptoms related to the psychological profile, indicating, therefore, little significance regarding the study hypothesis that positive mental health indicators would be directly related to higher levels of physical activity.
Keywords: Physical activity; University students; Anxiety; Depression; Mood states; Stress